Comparative Evaluation of 10 Prehospital Triage Strategy Paradigms for Patients With Suspected Acute Ischemic Stroke. Issue 12 (18th June 2019) - Schlemm, Ludwig; Endres, Matthias; Scheitz, Jan F.; Ernst, Marielle; Nolte, Christian H.; Schlemm, Eckhard
Abstract : Background: The best strategy to identify patients with suspected acute ischemic stroke and unknown vessel status (large vessel occlusion) for direct transport to a comprehensive stroke center instead of a nearer primary stroke center is unknown. Methods and Results: We used mathematical modeling to estimate the impact of 10 increasingly complex prehospital triage strategy paradigms on the reduction of population‐wide stroke‐related disability. The model was applied to suspected acute ischemic stroke patients in (1) abstract geographies, and (2) 3 real‐world urban and rural geographies in Germany. Transport times were estimated based on stroke center location and road infrastructure; spatial distribution of emergency medical services calls was derived from census data with high spatial granularity. Parameter uncertainty was quantified in sensitivity analyses. The mothership strategy was associated with a statistically significant population‐wide gain of 8 to 18 disability‐adjusted life years in the 3 real‐world geographies and in most simulated abstract geographies (net gain −4 to 66 disability‐adjusted life years). Of the more complex paradigms, transportation of patients with clinically suspected large vessel occlusion based on a dichotomous large vessel occlusion detection scale to the nearest comprehensive stroke center yielded an additional clinical benefit of up to 12 disability‐adjusted life years in some rural but not in urban geographies. Triage strategy paradigms based on probabilistic conditional modeling added an additional benefit of 0 to 4 disability‐adjusted life years over less complex strategies if based on variable cutoff scores. Conclusions: Variable stroke severity cutoff scores were associated with the highest reduction in stroke‐related disability. The mothership strategy yielded better clinical outcome than the drip‐'n'‐ship strategy in most geographies.